Mapping the scientific research on exercise therapy for Alzheimer’s disease: a scientometric study of hotspots and emerging trends - Song, Shi Long; Yu, Wen Bing; Cai, Xin Min; Ma, Jie; Zou, Lu Lu; Gao, Li Li; Li, Shi Ming (Frontiers in Aging Neuroscience, 2025)
BackgroundAlzheimer’s disease (AD) is the most common form of dementia globally, placing a substantial economic burden on patients and society. Exercise serves as an adjuvant therapy for AD with a low incidence of related adverse events. As a non-pharmacological intervention, it has demonstrated significant potential in the therapy of AD.ObjectiveThis study examines the key hotspots and emerging trends in exercise therapy for AD, offering valuable insights for researchers engaged in future research in this field.MethodsThe Web of Science Core Collection database was utilized to search for literature on exercise therapy for AD from January 1, 2000, to November 1, 2024, with 1,372 relevant articles being identified. And CiteSpace 6.2.R4 and VOSviewer were used to evaluate the bibliometric indicators.ResultsSince 2000, the number of publications in the field of exercise therapy for AD has been increasing. In addition to the well-known areas of research, such as the impact of exercise on cognitive function, the combination of exercise and medication therapy, the effects of exercise on specific symptoms, and the exercise with music therapy, the field may also focus on more novel topics. These include the integration of the design and implementation of exercise interventions, exercise and dendritic spines, and exercise and neurophysiological mechanisms. Furthermore, an analysis of emerging keywords reveals that the current main research direction is exploring the specific physiological mechanisms through which exercise affects AD. This includes three emerging trends: the impact of exercise on cognitive impairment in AD patients, the effects of exercise on brain-derived neurotrophic factor (BDNF) and Amyloid beta, and the influence of exercise on Stress and neuroinflammation.ConclusionThe research results indicate that interventions using exercise to alleviate the negative symptoms of AD, as well as combining exercise with medication for therapy, are gaining increasing attention from researchers. Meanwhile, novel topics such as exercise and music therapy, the design and implementation of exercise interventions, and neurophysiological mechanisms should also attract scholarly interest. Additionally, exploring the physiological mechanisms behind exercise therapy for AD could be a key focus for future research.